2012
DOI: 10.1093/cid/cis342
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Visit Rates for Abscess Versus Other Skin Infections During the Emergence of Community-Associated Methicillin-Resistant Staphylococcus aureus, 1997–2007

Abstract: Due to a flaw in the International Classification of Diseases, Ninth Revision, Clinical Modification coding system, epidemiology of skin and soft-tissue infections (SSTIs) has conflated abscess with other SSTIs. We analyzed emergency department visits during 1997-2007, finding that the odds of abscess relative to any other diagnosis increased 11% per year, or 3.1-fold, whereas other SSTIs increased minimally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 10 publications
1
35
0
Order By: Relevance
“…were treated with I&D). This is consistent with the results of a single-center study which also found that I&D was performed at 22% of skin infection visits 8. Our analysis reveals substantial regional variation in the frequency of skin infection relative to other diagnoses, in the frequency of abscess among skin infection, and the likelihood of use of anti-CA-MRSA antibiotics, with the effects of the CA-MRSA epidemic most apparent in the South (Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…were treated with I&D). This is consistent with the results of a single-center study which also found that I&D was performed at 22% of skin infection visits 8. Our analysis reveals substantial regional variation in the frequency of skin infection relative to other diagnoses, in the frequency of abscess among skin infection, and the likelihood of use of anti-CA-MRSA antibiotics, with the effects of the CA-MRSA epidemic most apparent in the South (Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…With the increased prevalence of communityacquired MRSA (CA-MRSA), new questions arose regarding the risk of bacteremia in children with SSTIs [15][16][17][18]. Wathen and Halloran [13] reviewed charts for 385 patients with cellulitis and found that, of 129 patients (33.5%) with blood cultures obtained, none were positive and 4 were contaminated (1%).…”
Section: What Is the Yield Of Blood Cultures?mentioning
confidence: 99%
“…The frequency of abscesses due to CA-MRSA is increasing [16][17][18]. Prior to this increase, several…”
Section: Abscessmentioning
confidence: 99%
“…Subjects with an International Classification of Diseases, Version 9 code consistent with an SSTI (680.xx-682.xx) were initially identified; these diagnosis codes have been similarly used in multiple investigations of SSTI (18)(19)(20)(21). Subjects with a disposition of OU admission were screened.…”
Section: Subject Identification and Data Collectionmentioning
confidence: 99%